DRYING AND BURNING CHARACTERISTICS OF IPÊ BRANCO WOOD CYLINDERS - Castro, A.; Costa, F. S. (Revista de Engenharia Térmica, 2007)
This work presents the drying and burning characteristics of Ipê Branco (Tabebuia rosco-alba) wood cylinders. The drying, self-ignition, flaming and smoldering phases under a constant heat flux are analysed. The effects of moisture content on characteristic times, mass evolution and consumption rates are described. The Ipê Branco cylinders presented flaming only for moisture contents equal or below 40% on dry basis. It is verified that the moisture content influences significantly the drying and flaming phases of the burning process of the Ipê Branco cylinders, however there is no significant effect on smoldering rates